Communication Patterns Between Religious Communities in Strengthening Harmony in Gangsiran Hamlet, Parang Magetan District - Hesti Setiyoningtias (Edumaspul: Jurnal Pendidikan, 2024)
The focus of the problem in this study is how the pattern of communication between religious communities in strengthening harmony in Gangsiran Hamlet, Mategal Village, Parang District, Magetan Regency. This study aims to find out the types of communication patterns and to describe the communication barriers used between religious communities in strengthening harmony in Gangsiran Hamlet, Mategal Village, Parang Magetan District. The research method used in this study is a qualitative descriptive research method. The subject of this study is the community in Gangsiran Hamlet, Parang Magetan District. The data analysis determination techniques used are data reduction, data presentation, and conclusion drawn. This study shows that the relationship between religious communities in Gangsiran Hamlet, Mategal Village, Parang Magetan District has a harmonious relationship. The communication used by the people of Gangsiran Hamlet with the administrators of the village uses various communication patterns. The communication patterns used are, primary (face-to-face), secondary (through radio communication media), linear (one-way communication using radio), and circular (feedback or feedback is needed ). In communicating, of course, there are obstacles experienced by the pesanggrahan administrators. The communication barriers experienced are, semantic (misinterpretation that causes differences of opinion), and technical (lack of infrastructure in the communication process).